The teaching of gerontogeriatric nursing in Brazil from 1991 to 200 seen under the complexity of Edgar Morin - Santos, Silvana Sidney Costa (Online Brazilian Journal of Nursing, 2005)
The present study had the following objectives: to identify the characteristics of gerontogeriatric nursing such as exhibited on Brazilian Nursing Journals; and to draw a reflection on the teaching of gerontogeriatric nursing in undergraduation courses, based on identified characteristics as seen under the Complexity of Edgar Morin. A qualitative research, it had as a data-source 9 proceedings volumes of Brazilian Nursing Congresses (281 abstracts, of which 260 are on gerontogeriatrics and 21 on the teaching of gerontogeriatric nursing), plus 7 national nursing publications: “Revista Texto e Contexto em Enfermagem”, “Revista da Escola de Enfermagem da USP”, “Revista Gaúcha de Enfermagem”, “Revista Enfermagem da UERJ”, “Revista da RENE”, REBEN, “Revista Latino-Americana de Enfermagem” (186 Journal issues of which 88 articles on gerontogeriatrics and 9 covering the teaching of gerontogeriatric nursing) for the 1991-2000 period. The main body of this article comprised 16 scientific articles on the teaching of gerontogeriatric nursing, where software was used for a qualitative analysis – QRS- NUD*IST4. Results made possible to perceive teaching during the research period conducted as: the mandatory subject, the introduction of specific contents in various subjects, the participation on extension work, and extra-curriculum training stages. Contents were presented through the themes: the aged; growing old; old age; gerontology and geriatrics; gerontogeriatric nursing turned to conceptual aspects; work process, nursing process, care to the elder – in houses for the aged, dependent and undergoing surgery, family care, care given to family carers, and care given at home. Such findings strongly support the thesis that Brazilian nursing already understands the gerontogeriatric field as a void still to be filled, requiring roads for an autonomous and/or multidisciplinary team work professional action, and interdisciplinary and/or transdisciplinary work. To think of the teaching of gerontogeriatric nursing or any other subject matter, in Nursing, using the Principles of Edgar Morin’s Complexity is tantamount to perceiving educative teaching as trying to convey a culture enabling the future worker to: understand the human condition; think in a contextualized, open, globalized, ethics, dialogic, recursive and hologrammatic form; and, to direct this worker towards: acquiring qualifications, learning how to do research, to develop practical classes and/or training stages, and other activities turned to the care of the elderly, reconnecting the various knowledges with other disciplines, having as the main target of this educational teaching the human, professional, and ecological care.